Implementing Floating Collections: To Float or to Sink? A case study - Burman, Emma; Brage, Christina (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
This case study describes the implementation process of Floating Collection as a way to work with collections at Linkoping University Library, from the first discussion, further to the implementation of a large-scale test, and to the Boards decision to permanently work with Floating Collection. The study shows mainly advantages but also some concerns, experiences that other libraries also report.